Pengaruh Kualitas Layanan dan Promosi Online terhadap Kepuasan Pelanggan pada PT Tirta Asasta Depok (PERSERODA) - Farhan Aiman Cahyono; Ade Sri Mulyani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Service quality and online promotion play a crucial role in influencing customer satisfaction. Their application extends beyond merely boosting sales volume; they are also essential in observing customer behavior and fulfilling their needs by understanding the types and qualities of services that customers desire. This study aims to investigate the impact of service quality and online promotion on customer satisfaction at PT. Tirta Asasta Depok (PERSERODA). The research methodology utilized is quantitative statistical analysis. The population for this study comprises the customers of PT. Tirta Asasta Depok (PERSERODA). Data collection methods include interviews, questionnaires, documentation, and observation, with the primary data collection being done through questionnaires. Data processing is conducted using SPSS 16.0 software with multiple linear regression analysis techniques. The results indicate that service quality significantly influences customer satisfaction and that online promotion also has a significant effect on customer satisfaction. Furthermore, both service quality and online promotion together have a simultaneous and significant impact on customer satisfaction.